Digitalization in the labor migration process in Bangladesh to stop the manpower scamming in overseas employment: a study on ‘Ami Probashi’, a project of Bangla Trac Group - Ahmed, K.M. Tasfique (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.